2016
DOI: 10.1128/jvi.01979-15
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of PML Nuclear Bodies in Innate Immune Signaling

Abstract: Research in the last 2 decades has demonstrated that a specific organelle of the cell nucleus, termed PML nuclear body (PML-NB) or nuclear domain 10 (ND10), is frequently modified during viral infection. This correlates with antagonization of a direct repressive function of individual PML-NB components, such as the PML, hDaxx, Sp100, or ATRX protein, that are able to act as cellular restriction factors. Recent studies now reveal an emerging role of PML-NBs as coregulatory structures of both type I and type II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
177
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(179 citation statements)
references
References 35 publications
2
177
0
Order By: Relevance
“…Previous studies have shown that PML is a potent effector of IFN in that it is induced by IFN and that the suppression of viral replication in PML −/− cells is significantly reduced compared with that observed in parental PML +/+ cells (5,31,32,61). Because SP100 is independently induced by IFN, the question arose concerning its role as an effector of IFN.…”
Section: Viral Replication Is Suppressed In Sp100 −/− Cells Pretreatementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that PML is a potent effector of IFN in that it is induced by IFN and that the suppression of viral replication in PML −/− cells is significantly reduced compared with that observed in parental PML +/+ cells (5,31,32,61). Because SP100 is independently induced by IFN, the question arose concerning its role as an effector of IFN.…”
Section: Viral Replication Is Suppressed In Sp100 −/− Cells Pretreatementioning
confidence: 99%
“…They consist of an outer shell composed of PML, a set of constant proteins (e.g., CBP, Daxx, SP100 nuclear antigen), and various other proteins depending on the particular stress or function of the ND10 bodies (1)(2)(3)(4)(5)(6)(7). ND10 bodies have drawn attention recently, in large part because of increasing evidence suggesting that they sense and respond to infection (5,8). For example, ND10 bodies have been shown to assemble de novo at herpes simplex virus 1 (HSV-1) DNA newly released from capsids at nuclear pores (9,10).…”
mentioning
confidence: 99%
“…The first interpretation would assume that host cells have the potential to respond to different viruses using a common mechanism, but each virus has specific countermeasures that prevent genome targeting by nuclear antiviral factors to different degrees, explaining apparent differences in the cellular response. This view has been propagated to some extent in the literature [5,6,25]. An alternative interpretation is that the observed differences in a set of viral systems indeed reflect distinct cellular responses (or absence thereof) against each virus.…”
Section: Possible Mechanisms For Distinct Cellular Responses: Detementioning
confidence: 99%
“…Importantly, some (but not all) of the observations appear similar among different DNA viruses, leading to a generalized concept in which viral DNA genomes are immediately targeted by a set of nuclear antiviral factors in a common way [5,6,25]. By carefully reading the literature, however, we reach the conclusion that for many DNA viruses, the interplay between nuclear antiviral factors and incoming viral genomes immediately following genome import remains to be shown.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation